Perkembangan Dan Pembelajaran Bahasa Anak Menuju Bahasa Mitos - Arif Hidayat (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2015)
Abstract: The development pattern of a child into the identity not only formed through psychological symptoms, but there are various relationships that shape it. This paper is intended to uncover the connection between psychology, anthropology, and languages. Three domains was a marking on person’s identity. Interralation between otherness, the order of the imaginary and the symbolic is always inherent in the concept of myhth. The formation of the myth itself by language and tagging the objects with the ability of a person’s interpretation is done subjectively. Language as a system of knowledge constructing some tagging become a social discourse, which is believed to be either in the form the sacred, morality, and rationality. Therefore, development and coaching tagging the objects during chillhood become invaluable knowledge as learning/ The way they mark (with the ability to understand) objects will have effects to create a new sign at a later date. Keywords: children’s language, psychology, development, anthropology, language of myth.